NATURE — AN INSEPARABLE PART OF HUMAN LIFE - Sodiqova Durdona Bahtiyorjon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation. This article, written from the perspective of a 6th grade student from Uzbekistan, explores the vital role of nature in human life. The author examines how nature provides humanity with clean air, fresh water, food, and natural resources, while also drawing attention to the growing environmental threats caused by industrialisation and human carelessness. The article encourages every individual — especially young people — to take personal responsibility for protecting and preserving the natural world for future generations.